Penggunaan Instagram sebagai Media Promosi Perpustakaan SMA Negeri 20 Surabaya: Bahasa Indonesia - Permata Wahyuniarti; Hartini, Pri (Ikatan Pustakawan Indonesia, 2023)
Promotion activities are carried out to introduce library information products and services to school residents and the wider community who is using social media. The library where a place for knowledge and information center, it can be used to attract the interest of the school residents to visit the library by social media. Through the promotion using social media, the library will be able to reach users widely so, the collections and services can be utilizest optimally. These includes facilitating the dissemination of information and the agenda of library activities that will be implemented. Social media also can be used as an interactive place and an active participation of users in library development through critics and suggestions. This study discuss the use of Instagram as a media promotion for the library of SMA Negeri 20 Surabaya. The purpose of this study is to determine the use of Instagram in promotion activities and the features that is used by the SMA Negeri 20 Surabaya library. The benefits of this research are being able to manage and utilize social media as a promotion media for library activities. This research method use a descriptive approach and a qualitative approach. The subjects of this study were the students and teachers of SMA Negeri 20 Surabaya. Data collection techniques in this study are questionnaire on google form, literature study and documentation. The result of this research is the library in SMA Negeri 20 Surabaya has used Instagram as a medium for promoting facilities, collection materials and library activities with the @smandaluhlib account. The features used in Instagram are photos and videos and comment fields.